Neurokinin-1 receptor antagonists for postoperative nausea and vomiting: a systematic review and meta-analysis - Murakami,Chiaki (2020)
Abstract Background: Postoperative Nausea and Vomiting (PONV) is a common complication of general anesthesia. Several kinds of antiemetics, including 5-Hydroxytryptamine3 (5-HT3) receptor antagonists, and Neurokinin-1 (NK-1) receptor antagonists have been used to treat PONV. Objectives: To compare the antiemetic effect of NK-1 receptor antagonists, including fosaprepitant. Data sources: Online databases (PubMed, MEDLINE, Scopus, The Cochrane Library databases) were used. Study eligibility criteria, participants, and interventions: Randomized Controlled Trials (RCTs) performed in patients over 18 years with ASA-PS of I‒III, aimed to assess the efficacy of antiemetics including NK-1 receptor antagonists and 5-HT3 receptor antagonists, and compared the incidence of PONV were included. Study appraisal and synthesis methods: All statistical assessments were conducted by a random effect approach, and odds ratios and 95% Confidence Intervals were calculated. Results: Aprepitant 40 mg and 80 mg significantly reduced the incidence of vomiting 0‒24 hours postoperatively (Odds Ratio [OR = 0.40]; 95% Confidence Interval [95% CI 0.30‒0.54]; p < 0.001, and OR = 0.32; 95% CI 0.19‒0.56; p < 0.001). Fosaprepitant could also reduce the incidence of vomiting significantly both 0‒24 and 0‒48 hours postoperatively (OR = 0.07; 95% CI 0.02‒0.24; p < 0.001 and OR = 0.07; 95% CI 0.02‒0.23; p < 0.001). Limitations: Risk factors for PONV are not considered, RCTs using multiple antiemetics are included, RCTs for fosaprepitant is small, and some bias may be present. Conclusions and implications of key findings: Aprepitant and fosaprepitant can be effective prophylactic antiemetics for postoperative vomiting. However, more studies are required for higher-quality meta-analyses. Systematic review registration number: CRD42019120188.